Agribusiness model approach to territorial food development (2011)
Several research efforts have coordinated the academic program of Agricultural Business Management from the University De La Salle (Bogota D.C.), to the design and implementation of a sustainable agribusiness model applied to food development, with territorial projection. Rural development is considered as a process that aims to improve the current capacity and potential of the inhabitant of the sector, which refers not only to production levels and productivity of agricultural items. It takes into account the guidelines of the Organization of the United Nations “Millennium Development Goals” and considered the concept of sustainable food and agriculture development, including food security and nutrition in an integrated interdisciplinary context, with holistic and systemic dimension. Analysis is specified by a model with an emphasis on sustainable agribusiness production chains related to agricultural food items in a specific region. This model was correlated with farm (technical objectives), family (social purposes) and community (collective orientations) projects. Within this dimension are considered food development concepts and methodologies of Participatory Action Research (PAR). Finally, it addresses the need to link the results to low-income communities, within the concepts of the “new rurality”.